Local Wisdom Recognition in Inter-Ethnic Religious Conflict Resolution in Indonesia from Islah Perspective - Arbanur Rasyid; Rayendriani Fahmei Lubis; Muhammad Wandisyah R. Hutagalung; Maulana Arafat Lubis; Mohd Roslan Mohd Nor; Afifah Vinandita (Institut Agama Islam Negeri Batusangkar, 2023)
Indonesia is a culturally diverse country that consists of at least 1.340 tribes and ethnicities, which can potentially lead to the emergence of conflicts. This study aimed to identify the causes of conflict in society, patterns of local wisdom in conflict resolution, and patterns of conflict resolution in Surabaya and Bali from the perspective of islah. Data were collected through observation, interviews, and document studies. Data analysis was carried out in several stages, including data reduction, data display, and verification. The result of this research showed that economic disparities, a lack of understanding of religion, and unfair treatment were the root of inter-ethnic conflict in the two regions. Local wisdom was used by communities to resolve conflicts in their area, including using a religious approach of praying together, listening to preaching or lecture about moderate Islam, consulting traditional, religious, and government leaders, and applying a state approach of administrative data collection or KIPEM administration. In addition, the local community also used interfaith dialogue with former terrorists, Jancuk Terrorist campaign by Bonek, and Tat Twam Asi to resolve conflict. Those conflict resolutions exemplified the procedures and methods of islah in Islamic law which aimed at resolving inter-ethnic disputes that arose in these two regions.